Flexible and stretchable liquid metal electrodes working at sub-zero temperature and their applications - Xiao, Peng; Kim, Ju Hyung; Seo, Soonmin (Materials, 2021)
We investigated characteristics of highly flexible and stretchable electrodes consisting of Galinstan (i.e., a gallium-based liquid metal alloy) under various conditions including sub-zero temperature (i.e., <0◦C) and demonstrated solar-blind photodetection via the spontaneous oxidation of Galinstan. For this work, a simple and rapid method was introduced to fabricate the Galinstan electrodes with precise patterns and to exfoliate their surface oxide layers. Thin conductive films possessing flexibility and stretchability can be easily prepared on flexible substrates with large areas through compression of a dried suspension of Galinstan microdroplets. Furthermore, a laser marking machine was employed to facilitate patterning of the Galinstan films at a high resolution of 20 µm. The patterned Galinstan films were used as flexible and stretchable electrodes. The electrical conductivity of these electrodes was measured to be ~1.3 × 106 S m−1, which were still electrically conductive even if the stretching ratio increased up to 130% below 0◦C. In addition, the surface oxide (i.e., Ga2O3 ) layers possessing photo-responsive properties were spontaneously formed on the Galinstan surfaces under ambient conditions, which could be solely exfoliated using elastomeric stamps. By combining Galinstan and its surface oxide layers, solar-blind photodetectors were successfully fabricated on flexible substrates, exhibiting a distinct increase of up to 14.7% in output current under deep ultraviolet irradiation (254 nm wavelength) with an extremely low light intensity of 0.1 mW cm−2, whereas no significant change was observed under visible light irradiation.
Keywords: Electrical conductivity; Electrically conductive; Laser marking machines; Photo-responsive property; Solar-blind photodetectors; Stretchable electrodes; Sub-zero temperatures; Visible-light irradiation; Flexible electronics photodetectors; Galinstan; Gallium alloys; Liquid metals; Solarblind photodetection